OPTIMALISASI EDITING GREEN SCREEN MENGGUNAKAN TEKNIK LIGHTING PADA CHROMA KEY - Arin Yuli Astuti; Sukoco .; M.Suyanto . (MULTITEK INDONESIA, 2016)
In the film world greenscreen or bluescreen is already widely in use as a background making technology . Utilization of this technology is very great because filmmakers can imagine changing the background to the shape or the desired atmosphere without having to perform image capture directly to the location . Chroma key is a technique for combining two images made with a video camera as well , in which a background color of an image to remove (made transparent ) , was replaced by another image behind it. Deficiencies that exist in the chroma key is that at the time of editing of the hair . Here the author tries to do research on how to minimize the weaknesses mengilangkan edge portion of hair at the time of editing green screen by optimizing lighting / lighting .